Fabrication of novel PNIPAM@GO microspheres loaded with dual drugs featuring on‐demand drug release capability. Issue 27 (26th April 2022) - Jiang, Yulin; Wang, Jing; Wang, Juehan; Zhuang, Yi; Qi, Lin; Feng, Ganjun; Zhang, Li
Abstract: In this research, we successfully prepared a new kind of core‐shell microspheres (PNIPAM@GO) composed of hydrophilic poly (N‐isopropyl acrylamide) (PNIPAM) nanoparticles as the core and amphiphilic graphene oxide (GO) nanosheets as the shell through hydrogen bonding and self‐assembly in organic solvent. The temperature‐sensitive behavior of the PNIPAM core made its average size decrease from 888.3 nm to 630.3 nm with temperature increasing from 25°C to 50°C. And the GO shell could give PNIPAM@GO microspheres remarkable photothermal effects in water under NIR laser irradiation (808 nm) for 20 min. Further, doxorubicin (DOX) and 5‐fluorouracil (5‐FU) were loaded into the core and the shell with loading efficiency of 81% and 11%, respectively. By turning on/off NIR irradiation, the PNIPAM@GO microspheres could respond to the heat generated from GO shell by volume shrinkage, thus on‐demand controlling the drug release. The in vitro biological assessment verified that the samples prepared here were biocompatible. The developed platform shows a potential application in chemo‐photothermal therapy of cancers in the future. Abstract : Schematic illustration of the fabrication and characteristics of the PNIPAM@GO microspheres.